Synthesis and crystal structure of [Sr(urea)(NO3)2]n - Aysanem Bektursinova; Zulfiya Djumanazarova; Zamira Uzakbergenova; Jamshid Ashurov; Akram A Khan; Shakhnoza Kadirova; Batirbay Torambetov (Acta Crystallographica Section E: Crystallographic Communications)
The crystal structure of poly[di-μ2-nitrato-μ2-urea-strontium(II)], [Sr(NO3)2(CH4N2O)]n, was determined using single-crystal X-ray diffraction. Crystallizing in the orthorhombic space group Aba2, the asymmetric unit consists of an SrII cation, two nitrate anions, and two half urea molecules. The SrII cation adopts a distorted decahedral geometry coordinated by ten oxygen atoms, with Sr—O bond lengths ranging from 2.573 (3) to 2.847 (5) Å. The nitrate anions act as bidentate ligands, displaying both terminal and bridging coordination modes. The structure features a robust coordination network supported by hydrogen bonding. These results provide insight into the coordination behaviour of SrII with nitrate and urea ligands, contributing to the understanding of supramolecular architectures in metal–organic frameworks (MOFs).